2021
DOI: 10.7150/ijms.52752
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Hirudin plus Aspirin versus Warfarin in the secondary prevention of Cardioembolic Stroke due to Nonvalvular Atrial Fibrillation: A multicenter prospective cohort study

Abstract: Background: To investigate the efficacy and safety of hirudin plus aspirin therapy compared with warfarin in the secondary prevention of cardioembolic stroke due to nonvalvular atrial fibrillation (NVAF). Methods: Patients with cardioembolic stroke due to NVAF were prospectively enrolled from 18 collaborating hospitals from Dec 2011 to June 2015. Fourteen days after stroke onset, eligible patients were assigned to the hirudin plus aspirin group (natural hirudin prescribed as the traditional Chinese medicine Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Unless there is a contraindication to heparin (such HIT) or injections, non-heparin anticoagulants are not typically utilised during pregnancy. Danaparoid is a derivative of that is not placenta-permeable (23).…”
Section: Guidelines For the Diagnosis Management And Prevention Of Ve...mentioning
confidence: 99%
“…Unless there is a contraindication to heparin (such HIT) or injections, non-heparin anticoagulants are not typically utilised during pregnancy. Danaparoid is a derivative of that is not placenta-permeable (23).…”
Section: Guidelines For the Diagnosis Management And Prevention Of Ve...mentioning
confidence: 99%
“…Salvianolic acid A decreased the expression of PAC-1 and CD62p and reduced platelet aggregation induced by ADP and thrombin (Zhou et al, 2020). In addition, studies have shown that hirudin, the main component of Maixuekang (four grains each time, tid), is a highly specific thrombin inhibitor, which inhibits platelet adhesion and aggregation, reduces blood viscosity, reduces inflammatory injury of vascular endothelial function, and improves plaque stability (Ge et al, 2012;Yan et al, 2012;Song et al, 2021). However, these studies are still not sufficiently detailed; thus, it is necessary to explore other potential targets.…”
Section: Evidence From Clinical Trials and Safety Assessmentsmentioning
confidence: 99%